Failure to demonstrate that memory improvement is due either to aerobic exercise or increased hippocampal volume. - KENNY, ROSE ANNE; LAWLOR, BRIAN (My University, 2011)
We read with interest the article in PNAS, ?Exercise training increases size of hippocampus and improves memory? by Erickson et al. (1). It is a noteworthy finding that over a 1-y period anterior hippocampal volume increased by 2% in the aerobic exercise group, whereas it decreased by 1.4% in the stretching control group. However, contrary to both the title and abstract, there is virtually no evidence in this article that exercise improved memory.
PUBLISHED
Keywords: brain derived neurotrophic factor; brain derived neurotrophic factor